Learning Outcomes Management in Vocational School - Darul Prayogo (Camarines Sur Polytechnic Colleges, 2023)
This research addresses the suboptimal learning outcomes observed in the Politeknik Ilmu Pelayaran Semarang technical drawing course, focusing on the interplay of lecturer performance, student engagement, and curriculum design. The primary objective is to enhance learning outcomes for Level I Cadets during the 2023 academic year. The study encompasses 103 Level I Cadets enrolled in the Engineering Study Program, utilizing a total sampling technique. Data collection involves a questionnaire to assess the Engineering drawing course's effectiveness. The analytical approach employs percentage descriptive techniques and regression methods, including partial and simultaneous tests, subject to meeting prerequisite test requirements such as normality, heteroscedasticity, linearity, and multicollinearity. Results indicate that lecturer and student factors and environmental elements significantly influence learning outcomes in technical drawing. However, curriculum factors do not exhibit a notable impact on learning outcomes. Collectively, lecturer performance, student engagement, curriculum design, and environmental factors jointly contribute to learning outcomes by 39%, with the remaining 61% influenced by unexplored variables such as cost, organizational climate, socio-culture, and education management. In conclusion, this study establishes a link between lecturer performance, student engagement, and the environment with learning outcomes in technical drawing courses. Conversely, curriculum factors show no significant influence. Recommendations include optimizing the roles of lecturers and students and enhancing the educational environment to foster a conducive learning atmosphere within the dormitory setting.